Effect of Additional Herbal Mix on Feed on Physical Quality of Broiler Meat - Ayu Lestari; Muh. Rafli; Muhammad Nur Hidayat (Chalaza Journal of Animal Husbandry, 2022)
Physical characteristics or physical properties of meat include pH, cooking loss, and texture, while organoleptic qualities include color, taste, texture, and aroma.These factors will simultaneously determine the quality of meat in livestock. This study aims to determine the effect of giving a combination of herbs, mineral zinc, expired milk powder, and vitamin C on the physical quality of broiler meat. This research was conducted at the Samata Integrated Farming System (SIFS), Jalan Veteran Bakung, Samata Village, Gowa Regency. Physical quality testing of meat was carried out at the Laboratory of Animal Products Technology, Universitas Islam Negeri Alauddin Makassar. The research design used in this study was a completely randomized design (CRD) with four treatments and five replications, each replication consisting of 2 broilers with treatment P0= commercial feed (Control), P1 = commercial feed + 1% herbs, P2= commercial feed + 2% herbs and P3= commercial feed + 3% herbs. Meat sampling was carried out on day 35 for analysis of physical quality including pH value, cooking loss, and meat tenderness. Data analysis used analysis of variance (ANOVA) and continued with Duncan's test. The results showed that the addition of a combination of mixed herbs to broiler feed had a significant effect (P0.05) on pH but had no significant effect (P0.05) on cooking loss and meat tenderness. Duncan’s test results showed that the pH value with P0 treatment was significantly different (P0.05) with P1, P2, and P3. All the treatments with different percentages of the herbal mix did not show significant differentiation between them.